2009
DOI: 10.1245/s10434-009-0606-2
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Features of Breast Cancer Differ by Molecular Subtype

Abstract: Tumor presentation varies among molecular subtypes; this information may be useful in selecting local therapy. Neoadjuvant therapy and lymph nodes evaluation before surgery or neoadjuvant therapy are likely to be beneficial in HER-2-overexpressing tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
117
3
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 13 publications
8
117
3
8
Order By: Relevance
“…Unlike some of the previous reports on the association of basal-like and HER -2 subtypes with more than three lymph node metastases (Wiechmann et al, 2009;Abdelkrim et al, 2010), we could not find any significant correlations between molecular subtype of the tumor and lymph node metastasis neither in univariate nor in multivariate analysis. However, there are studies that state the subtype of the tumor is not associated or only weakly associated with its size and lymph node metastasis, suggesting that subtype is "intrinsic" and predetermined (Bhargava et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike some of the previous reports on the association of basal-like and HER -2 subtypes with more than three lymph node metastases (Wiechmann et al, 2009;Abdelkrim et al, 2010), we could not find any significant correlations between molecular subtype of the tumor and lymph node metastasis neither in univariate nor in multivariate analysis. However, there are studies that state the subtype of the tumor is not associated or only weakly associated with its size and lymph node metastasis, suggesting that subtype is "intrinsic" and predetermined (Bhargava et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…The next prevalent subtype in our study was basal-like, followed by HER-2 and luminal B subtypes, respectively. These features are not distinct from breast cancer patients in western countries, where studies have shown that the prevalence of luminal A subtype varies from 47.9% (Munoz et al, 2009) to 75% (Nguyen et al, 2008), the luminal B subtype varies from 8 (Wiechmann et al, 2009) (Ihemelandu et al, 2007). A series conducted in west Africa (Nigeria and Senegal) reported a much higher prevalence of triple-negative (ER−, PR−, Her-2−) tumors (55%) and a lower prevalence of luminal A and luminal B phenotypes (27 and 2% respectively) (Huo et al, 2009).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The frequencies of lymph node metastasis were not significantly different between the four subtypes in the current study, the positive lymph node rate was around 40% among the four subtypes. Other studies showed that patients with HER2+ subtype and triple-negative are more likely to be lymph node positive disease [11][12][13] , we did not find such associations in the current study, possibly due to different study populations or samples selected.…”
Section: Discussioncontrasting
confidence: 88%
“…estrogen receptor(ER) and progesterone receptor (PR)) is diverse between Asian and Caucasian women. The ER+ tumor in Asian women is not as common as their Caucasian counterparts (Wiechmann et al, 2009;Telli et al, 2011;Chuthapisith et al, 2012). Previous evidences showed that ER+ tumor was associated with reproductive history (i.e., age at menarche, parity, and breastfeeding) while ER-tumor was not (Althuis et al, 2004;Tsakountakis et al, 2005).…”
Section: Discussionmentioning
confidence: 99%